2015
DOI: 10.1007/s12035-015-9505-7
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein T Deficiency Leads to Neurodevelopmental Abnormalities and Hyperactive Behavior in Mice

Abstract: Selenoprotein T (SelT) is a newly discovered thioredoxin-like protein, which is abundantly but transiently expressed in the neural lineage during brain ontogenesis. Because its physiological function in the brain remains unknown, we developed a conditional knockout mouse line (Nes-Cre/SelT) in which SelT gene is specifically disrupted in nerve cells. At postnatal day 7 (P7), these mice exhibited reduced volume of different brain structures, including hippocampus, cerebellum, and cerebral cortex. This phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…Together, these observations suggest that SelT expression is associated with cell plasticity, a process which requires increased metabolism and energy but which generates free radicals. Our recent studies performed in neuronal cells showed that SelT is required for oxidative stress tolerance and that its biosynthesis is coupled to mitochondrial function during differentiation . Therefore, SelT expression during cardiac tissue ontogenesis is likely involved in cardiomyocyte protection and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these observations suggest that SelT expression is associated with cell plasticity, a process which requires increased metabolism and energy but which generates free radicals. Our recent studies performed in neuronal cells showed that SelT is required for oxidative stress tolerance and that its biosynthesis is coupled to mitochondrial function during differentiation . Therefore, SelT expression during cardiac tissue ontogenesis is likely involved in cardiomyocyte protection and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several selenoproteins are highly expressed during development, and their loss has been associated with major anatomical alterations and functional defects in rodents . In particular, selenoprotein T (SelT or SELENOT) is a key thioredoxin‐like enzyme present in the endoplasmic reticulum, which is essential at early stage of mouse development . SelT is highly expressed in most embryonic organs, but declines gradually as the organs develop, to disappear in most adult tissues except the endocrine glands .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The so‐far elusive other selenoprotein essential for neurons may be selenoprotein T (SelT) (61). SelT is an ER‐ resident selenoprotein with a thioredoxin‐like structure and activity.…”
Section: Transgenic Mouse Studies Revealed Selenoprotein Functions Inmentioning
confidence: 99%
“…How exactly its deficiency impairs neurologic function is currently not known. A neural-specific knockout of SelT leads to hyperactive behavior and moderate signs of cell death during brain development, but epilepsy, loss of PV interneurons, and overt degeneration of cortical or hippocampal neurons have not been reported (61).…”
Section: Transgenic Mouse Studies Revealed Selenoprotein Functions Inmentioning
confidence: 99%